Food waste disposal units in UK households: the need for policy intervention. - Iacovidou,E; Ohandja,D-G; Voulvoulis,N (Science of the Total Environment, 2012)
The EU Landfill Directive requires Member States to reduce the amount of biodegradable waste disposed of to landfill. This has been a key driver for the establishment of new waste management options, particularly in the UK, which in the past relied heavily on landfill for the disposal of municipal solid waste (MSW). MSW in the UK is managed by Local Authorities, some of which in a less conventional way have been encouraging the installation and use of household food waste disposal units (FWDs) as an option to divert food waste from landfill. This study aimed to evaluate the additional burden to water industry operations in the UK associated with this option, compared with the benefits and related savings from the subsequent reductions in MSW collection and disposal. A simple economic analysis was undertaken for different FWD uptake scenarios, using the Anglian Region as a case study. Results demonstrated that the significant savings from waste collection arising from a large-scale uptake of FWDs would outweigh the costs associated with the impacts to the water industry. However, in the case of a low uptake, such savings would not be enough to cover the increased costs associated with the wastewater provision. As a result, this study highlights the need for policy intervention in terms of regulating the use of FWDs, either promoting them as an alternative to landfill to increase savings from waste management, or banning them as a threat to wastewater operations to reduce potential costs to the water industry.